Raising an HIV-infected child: associations between parental stress and child functional impairment - Phillips, Nicole Justine (Department of Psychology, 2015)
This project sought to achieve two major aims. First, I aimed to investigate the differences in functional, behavioural, and emotional impairment of HIV-infected, HAART-naive children compared to HIV-negative controls. Second, I aimed to investigate the levels of parental stress, depression, and quality of life related to caring for an HIV-infected child. Currently, there is limited research focusing on each of these topics. Nineteen HIV-positive (9 HAART-naÃ¯ve and 10 HAART-treated) parent-child dyads and 10 HIV-negative parent-child dyads were recruited. All participants were from socioeconomically disadvantaged backgrounds. Each parent and child completed measures related to the aims of this study. Parents completed measures related to their childâ€™s functional impairment (i.e.: CBCL, CIS, CMS) and questionnaires related to their parental well-being (i.e.: PSI, FRS, FSS, CES-D, WHO QoL). Children completed a comprehensive neuropsychological test battery. Statistical analyses revealed no significant between-group differences in terms of child functional, behavioural, and emotional impairment. These non-significant findings were confirmed by an in-depth qualitative review of three case studies. Statistical analyses also revealed no significant between-group differences with regards to parental stress, depression, and quality of life. The possibility of poor socioeconomic status (SES) explaining the lack of difference is discussed, as well as the possibility of potential protective factors.